2017
DOI: 10.1002/jmri.25604
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of segmental myocardial blood flow and myocardial perfusion reserve by adenosine‐stress myocardial arterial spin labeling perfusion imaging

Abstract: 2 Technical Efficacy: Stage 1 J. MAGN. RESON. IMAGING 2017;46:413-420.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 50 publications
(102 reference statements)
4
13
0
Order By: Relevance
“…Solid line is the 50 C isotherm, which can be assumed to be the thermal lesion contour. Dashed line represents the location of this contour when the blood perfusion term is included at a rate of 1719 ml/min/kg (maximum value reported in [17], but very similar to that measured in resting humans (1750 ± 860 ml/min/kg) using perfusion imaging techniques [19]).…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…Solid line is the 50 C isotherm, which can be assumed to be the thermal lesion contour. Dashed line represents the location of this contour when the blood perfusion term is included at a rate of 1719 ml/min/kg (maximum value reported in [17], but very similar to that measured in resting humans (1750 ± 860 ml/min/kg) using perfusion imaging techniques [19]).…”
Section: Resultssupporting
confidence: 54%
“…The increase in the difference over time is clearly noticeable. This case is relevant, since a recent study reported an even higher perfusion value for resting humans (1750 ± 860 ml/min/kg [19]). Figure 3 shows the progress of applied power (between 6 and 7 W) in the case of constant power ablation, and electrode temperature (50 C target) in the case of constant temperature ablation.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous attempts at myocardial ASL have employed a minimum TR of approximately six seconds to allow for a complete T1 recovery of the label (1664 ms at 3 T) . This long TR decreases scan efficiency and limits the total number of pairs to be averaged in a reasonable acquisition time.…”
Section: Introductionmentioning
confidence: 99%
“…Trained networks were tested on 144 unseen ASL images acquired at rest and during adenosine stress from 6 heart transplant recipients. Training, validation, and testing data were drawn from previously published studies (31)(32)(33), where manual segmentation and quantitative reginal MBF from all subjects were readily available.…”
Section: Network Architecturementioning
confidence: 99%